A model of incompressible isotropic hyperelastic material behavior using spline interpolations of tension-compression test data - Sussman, Theodore; Bathe, Klaus-Jürgen (Communications in numerical methods in engineering, 2009)
We present a model of incompressible isotropic hyperelastic material behavior based on a strain energy description separable in terms of logarithmic strains and piecewise spline interpolations of uniaxial tension–compression test data. Valuable attributes are that no fitting of model constants is carried out and the model replicates even physically complicated test data very accurately for small and large strains and for tension and compression. The model is well suited for use in finite element analysis. Copyright © 2008 John Wiley & Sons, Ltd.